Políticas institucionais de acessibilidade na educação superior: percursos e desafios para a inclusão de alunos com deficiência na UFMA - PEREIRA, Josenilde Oliveira (2017)
This study investigates inclusion process of students with disabilities in Federal University of Maranhão (UFMA) related to the support services context of the Accessibility Center, as part of an institutional policy of educational and social inclusion. The participants were 10 students with disabilities, 50% with low vision, 20% with physical disability, 10% with blindness, deafness and intellectual disability, respectively; 04 professors of UFMA who deal with disabled students, one from each Center (Center for Human Sciences (CCH), Center for Social Sciences (CCSo), Center for Biological and Health Sciences (CCBS) and Center for Exact Sciences and Technology (CCET)); 01 technician of the Campus City Hall; 01 technician of central library; 02 specialized professionals of the Accessibility Center and the coordinator of the Center. The instruments of data collection were semi-structured interviews, non-participant observation and questionnaire. The results reveal an advance in the institutional policies of accessibility and inclusion in the scope of the UFMA, especially from the Accessibility Center, acting as articulator of the actions for people with disabilities. It has identified quite contradictory paths that express antagonistic movement of capitalist society and impose challenges to be overcome by the Accessibility Center and the University itself, obstacles such as: expansion of the Center service; increasing investment on assistive technologies and specialized services; awareness campaigns and elimination of attitudinal barriers; campus infrastructure investment and the Center itself, expansion of the accessible library of the central library. The results shows that despite the existence of barriers that prevent the full participation of students with disabilities in university, the support service provided by the Center is a fundamental resource to ensure success in continuing higher education. There is a strengthening of the inclusion policy of people with disabilities within the University, mediated by the Accessibility Center.